Electroantennogram responses from olfactory receptors in Dαcus oleαe - Der Pers J.N.C. Υan; Haniotakis, G.E.; King Β.Μ. (ENTOMOLOGIA HELLENICA, 1984)
Substances found in Dacus oleae (Gmelin) (Diptera: Tephritidae) male or female flies which have been reported as pheromones, i.e. elicit some form of biological activity in laboratory or field bioassays, were tested with the electroantennogram technique (EAG). Substances of non-insect origin were also tested as possible pheromone candidates. All substances of insect or non-insect origin elicited an EAG response to both sexes of lab-cultured or wild insects but 1,7 dioxaspiro [5,5] undecane, the major pheromone component, has a lower response threshold value than all other compounds. At the maximum stimulus concentration the response to nonanal reaches a value higher than that elicited by all other compounds. EAG responses to various compounds, after receptor adaptation to the major pheromone compound and nonanal, showed that these two compounds are detected by different sets of receptors. Other comments on the sensitivity and specificity of antennal receptors are also presented.